2020
DOI: 10.1155/2020/6689023
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Ocular Morphological Parameters of Guinea Pig Eye with Edge Detection and Curve Fitting

Abstract: Aim. To identify the guinea pig eyeball with edge detection and curve fitting and devise a noncontact technology of measuring ocular morphological parameters of small experimental animal. Methods. Thirty-nine eyeballs of guinea pig eyeballs were photographed to obtain the anterior and posterior surface; transverse and sagittal planes after the eyeballs were eviscerated. Next, the eyeball photos were input into digital image analysis software; the corresponding photo pixels-actual length ratio was acquired by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The actual distance conversion coefficient (Figure 4D) could be obtained by taking points on the graduated scale at 10 mm distance repeatedly and calculating the average value. This above method was the same as the method of actual length-photo pixels conversion in Matlab image in our previous research [12] . Acquisition of ocular edge data manually Ten data points were manually taken in the target contour (corneal edge) to obtain the coordinates.…”
Section: Methods Of Actual Length-photo Pixels Conversionmentioning
confidence: 99%
See 3 more Smart Citations
“…The actual distance conversion coefficient (Figure 4D) could be obtained by taking points on the graduated scale at 10 mm distance repeatedly and calculating the average value. This above method was the same as the method of actual length-photo pixels conversion in Matlab image in our previous research [12] . Acquisition of ocular edge data manually Ten data points were manually taken in the target contour (corneal edge) to obtain the coordinates.…”
Section: Methods Of Actual Length-photo Pixels Conversionmentioning
confidence: 99%
“…Assuming the center of the cornea is a circle, circle fitting was applied, the real curvature radius of the cornea by means of the conversion coefficient could be obtained, just like we reported before [12] (Figure 5A, 5C, 5E).…”
Section: Calculation Of Curvature Radius By Circle and Conic Fittingmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, CNN architectures can avoid feature selection manually and automatically extract features, which are key elements to enable the intelligent tongue diagnosis system into TCM clinical practice. Although several previous studies have reported encouraging results using CNN methods to extract tongue image features for tongue colour (tongue body and tongue coating) classification [ 17 – 19 ], tongue image characteristic recognition (tooth-marked tongue [ 20 22 ], tongue cracking [ 23 ]), tongue image segmentation [ 24 31 ], and clinical application in herbal medicine [ 32 , 33 ], they usually ignore the quality of tongue images or implicitly assume the good quality of tongue images. Thus, the medical application of deep learning methods to the field of tongue diagnosis has not achieved much so far.…”
Section: Introductionmentioning
confidence: 99%